2011
DOI: 10.1002/art.30183
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 5 is critical for the development of lupus in MRL/lpr mice

Abstract: Objective. Interferon regulatory factor 5 (IRF-5) is a transcription factor that mediates intracellular signals activated by engagement of Toll-like receptors (TLRs). IRF5 polymorphisms are associated with an increased or decreased risk of systemic lupus erythematosus (SLE) in various human populations, but the precise role of IRF5 in SLE development is not fully understood. This study was undertaken to examine the role of IRF5 in the development of murine lupus.Methods. We crossed gene-targeted IRF5-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 49 publications
4
54
1
Order By: Relevance
“…3, 45 The interferon (IFN) signature of expressed genes is considered a useful prognostic biomarker for lupus, although signatures for IRF5 differ from the canonical IRF3/7 IFN induced expression pattern, and disease risk associated with IRF5 has been established in other autoimmune disorders in which the role of IFN is less clear. 3, 7, 45 These observations argue for a role for IRF5 beyond induction of IFN in dysregulation of chronic inflammation and autoimmunity, 46, 47 and the association of IRF5 with TNFα observed here in the control group, attenuation in SLE, and lack of association in RA suggests a disruption of control leading to chronic inflammation. 48 IRF5 acts as a master transcription factor downstream in the TLR pathway to induce proinflammatory cytokines including TNFα and IL-6.…”
Section: Discussionmentioning
confidence: 62%
“…3, 45 The interferon (IFN) signature of expressed genes is considered a useful prognostic biomarker for lupus, although signatures for IRF5 differ from the canonical IRF3/7 IFN induced expression pattern, and disease risk associated with IRF5 has been established in other autoimmune disorders in which the role of IFN is less clear. 3, 7, 45 These observations argue for a role for IRF5 beyond induction of IFN in dysregulation of chronic inflammation and autoimmunity, 46, 47 and the association of IRF5 with TNFα observed here in the control group, attenuation in SLE, and lack of association in RA suggests a disruption of control leading to chronic inflammation. 48 IRF5 acts as a master transcription factor downstream in the TLR pathway to induce proinflammatory cytokines including TNFα and IL-6.…”
Section: Discussionmentioning
confidence: 62%
“…These data further highlight the contribution of NF-κB signaling downstream of STING under homeostatic conditions and point to a constitutive role of this pathway in immune regulation. It is possible that other transcription factors, such as IRFs and STATs, may be engaged downstream of STING, but likely candidates IRF5, IRF1, STAT1, and STAT6 have previously been shown to promote lupus pathology (38)(39)(40)(41)(42), in contrast to the suppressive role of STING documented in this study. Thus, it is unlikely that transcriptional activity of any of these factors contributes to a STING-dependent suppressive pathway.…”
Section: Discussionmentioning
confidence: 70%
“…A reduction in Ly6C hi monocytes migrating to the peritoneal cavity due to down-regulated expression of chemokine receptors CXCR4 and CCR2 has also been observed in the absence of IRF5, which is thought to be a key initial event in the pathogenesis of the pristane-induced model (66). Concordant with this, the FcγRIIB -/-Yaa and FcγRIIB -/-murine lupus models showed that IRF5 is crucial for disease development, in particular IFNα production (67), as was also the case for Irf5 -/--MLR/lpr mice (68). In line with the genetic component of RA, multiple polymorphisms in the Irf5 locus have been associated with RA, although only to a weak/moderate extent (see Table 2).…”
Section: Irf5 and Slementioning
confidence: 74%